Enabling urban commons. Issue 3 (3rd July 2017) - Parker, Peter; Schmidt, Staffan
Abstract: An increasing interest in commons has generated a rich literature related to co- and participatory design (PD). Besides providing examples, cases and methods, this literature often displays interpretations that are recognisably engaged and political in which commons have acquired an additional symbolic value. In some cases this symbolic value propels more ambitious narratives in which other, post-industrial/post-collapse futures or utopian societal forms are prototyped or infrastructured. Although this literature highlights an important connection between collaborative design and collaborative governance, we hold that the conception of commons underpinning some of these efforts is not fully relevant in contemporary urban contexts. In the following article we describe the practical and normative issues raised by transferring the concept of commons to a contemporary urban setting. We critique aspects of how the concept has been invoked in Co-Design and PD but also seek to demonstrate how it may be applied constructively, paying due attention to both network and subtractive effects of shared resources and acknowledging interrelations with the public sector.